Effects of polymerized whey protein on survivability of Lactobacillus acidophilus LA‐5 during freeze‐drying. Issue 8 (24th July 2019) - Wang, Cuina; Wang, Mu; Wang, Hao; Sun, Xiaomeng; Guo, Mingruo; Hou, Juncai
Abstract: Probiotic cultures are commonly freeze‐dried for storage and distribution. However, freeze‐drying and subsequent storage are accompanied by a decline in cell viability. Whey protein (WP) or polymerized whey protein (PWP) was used to protect Lactobacillus acidophilus LA‐5 against damage during freeze‐drying process and the subsequent storage. The protection capacity and effects of polymerized whey protein protected freeze‐dried L. acidophilus LA‐5 on physiochemical properties of cow and goat milk yoghurts were evaluated in comparison with maltodextrin (MD). The survival rate of L. acidophilus LA‐5 after freeze‐drying decreased in the order of MD (80.91%) > PWP (69.86%) > WP (64.89%). The particles of WP‐ and PWP‐based freeze‐dried samples showed an average diameter of about 10 μm, which was significantly higher than that of MD‐based particles (1.5 μm). Both whey protein preparations showed higher protecting effect than MD at high humidity condition during the 180‐day storage. Addition of freeze‐dried L. acidophilus LA‐5 with the presence of WP or PWP improved the protein content and decreased spontaneous whey separation and syneresis significantly for both yoghurts. PWP‐protected L. acidophilus LA‐5 addition significantly improved the firmness and adhesiveness of the yoghurt. Freeze‐dried L. acidophilus LA‐5 mixed with PWP had higher survivability in yoghurts compared with the culture alone at the end of storage. Data indicated that whey protein can be used to protect probiotics during freeze‐drying and may also improve the physiochemical properties of the yoghurt. Abstract : Probiotic cultures are freeze‐dried for storage and distribution. WP has been used as protective agents to ensure the viability of probiotics during freeze‐drying process and storage. Results showed that whey protein may be a good ingredient to protect probiotics during freeze‐drying.